Paunang salita : pieces of a teacher's mind - Lumbera, Bienvenido, 4 0 16; 5 National Commission on Culture and the Arts (Philippines) (Intramuros, Manila, Philippines : Pambansang Komisyon para sa Kultura at mga Sining, 2014)
Philippine essays in English and Tagalog; festschrift in honor of Bienvenido Lumbera.
English and Tagalog.
Keywords: 2 -- 0; 6; Philippine essays (English).;Tagalog essays.;Philippine literature. -- 20; 20; 2